A new Bifidocoelotes species, with the description of the male of B. primus from Hong Kong, China (Agelenidae: Coelotinae) - Zhou, Yan-Chen; Yuen, Yan Ling; Zhang, Zhi-Sheng (Zootaxa, 2017)
Both sexes of two Bifidocoelotes species, Bifidocoelotes obscurus sp. nov. and B. primus (Fox, 1937), were collected in Hong Kong, China. The male of B. primus was previously unknown. Descriptions and illustrations of both species are provided and the generic diagnosis is revised.